Aboriginal myths : tales of the dreamtime - Reed, A. W. (Alexander Wyclif), 1908-1979. (Sydney : Reed, 1978)
Collection of myths arranged under headings; the great father, totemic ancestors, creation myths.
Includes bibliographical references.
Keywords: Australian Aboriginal tales & legends. Collections; Aboriginal Australians -- Folklore; Religion - Totemism; Stories and motifs - Creation / Cosmology; Sites - Dreaming tracks; Australia